Social work practice assessment, planning, intervention and review - Parker, Jonathan 1960- (Transforming social work practice., 2017)
This volume takes you step-by-step through the four main aspects of social work practice - Assessment, Planning, Intervention and Review - giving you a complete foundation in each. It will introduce you to each process in a clear and accessible way, supporting you to both reflect on and apply what you have learnt in practice across settings and service user groups.